The impact of the COVID-19 pandemic on health worker`s emotions and professional learning - Neves, Vanusa Nascimento Sabino (2020)
The objective was to discuss the most prevalent emotions in health professionals who are working on the front line of assistance to patients with COVID-19 and how they relate to learning needs for better professional training. A qualitative, descriptive and exploratory research was carried out based on the transcription and analysis of journalistic videos of public access and hosted on the You Tube platform in the first half of 2020. The content of the selected videos was referred to interviews provided by health professionals on the front line of fighting the pandemic for Brazilian newspaper companies. Among the results, it was evidenced that fear is a prevalent feeling among health professionals. Even in the face of strenuous work hours and fear, professionals have sought professional qualification through strategies that combine work and learning. It is concluded that the current health crisis has impacted professionals who seek to reconcile the feeling of fear with the functional duty, remaining steadfast in assisting patients with COVID-19 and seeking to train themselves to cope.